2016
DOI: 10.1149/2.0281607jss
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—On the Radiation Tolerance of AlGaN/GaN HEMTs

Abstract: The radiation tolerance of AlGaN/GaN high electron mobility transistors (HEMTs) fabricated on high quality, low threading dislocation density (TDD) ammonothermal GaN and hydride vapor phase epitaxy GaN substrates was studied and compared to the radiation response of devices on SiC substrates where the TDD is 10 4 times higher. Hall and transport measurements were performed as a function of 2 MeV proton fluence. The threading dislocation density had no effect on the radiation response. Comparing the results wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…These properties make III-V nitride an attractive electronic material for high-temperature and harsh-radiation environments. [1][2][3][4] Furthermore, gallium nitride (GaN) FETs have several advantages over traditional silicon FETs, including smaller size, lower weight, and higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These properties make III-V nitride an attractive electronic material for high-temperature and harsh-radiation environments. [1][2][3][4] Furthermore, gallium nitride (GaN) FETs have several advantages over traditional silicon FETs, including smaller size, lower weight, and higher efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may be a result of the reduced threading dislocation density in homoepitaxially grown GaN. 2,3,11 After irradiation, the mobility and resistivity drop to similar values to Sample A since impurity scattering is now the dominate factor. The sheet density (Figure 3h) drops at lower fluences due to increased electron donor traps in the AlGaN layer; however, these traps are deeper since they are still frozen out at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that switching to a AlN-passivated layer improves transistor performance, 10 while switching to a GaN substrate reduces threading dislocation densities by 4 orders of magnitude. 2,3,11 Previous experimental and theoretical studies have determined temperature dependent AlGaN/GaN Hall effect measurements result in the mobility being limited by piezoelectric scattering and ionized impurity scattering at low temperatures and phonon scattering at high temperatures. [12][13][14] However, the effect of radiation on these properties has not be examined.…”
mentioning
confidence: 99%
“…4 In addition, mobility has been shown to be degraded due to scattering induced by roughening of the AlGaN/GaN interface. 12 The reduction in gate leakage has also been previously observed and has been attributed to radiation-induced void formation as a result of Kirkendall diffusion in the Ni/Au gate metallization.…”
Section: -11mentioning
confidence: 99%
“…The fluence schedule ranged from 1 × 10 12 to 6 × 10 14 H + /cm 2 , and was designed to induce clear degradation in the DC characteristics based on prior work on GaN HEMTs. 4 To place this work into perspective, the maximum fluence tested represents >6,000 years in geostationary orbit. 8 Before and after irradiation, DC I-V sweeps were taken on all devices using a Keithley 4200 SCS.…”
mentioning
confidence: 99%